The Influence of Workload on Employee Performance with Motivation as a Moderating Variable (Case Study of PT Asuransi Jiwa Manulife Indonesia, Cab Ruko Bidex BSD) - Aryata, I Made; Tua, Rudy Bodewyn Mangasa; Manik, Cornelia Drumaya (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
PT Asuransi Jiwa Manulife Indonesia Cab Ruko Bidex BSD is part of PT Asuransi Jiwa Manulife Indonesia (Manulife Indonesia). The purpose of this study is to determine the indirect effect of Motivation as a moderating variable in strengthening or weakening Workload on Employee Performance using Linear Regression Analysis. From the results of the analysis, it is known that 1) Workload has a significant effect on Employee Performance with a calculated t value (4.264) > t table (2.006). Where workload has an effect of 26.4% on employee performance and 2) Motivation has a significant effect where Motivation Strengthens the Effect of Workload on Employee Performance with a calculated F value (16.488) > from F Table (3.179). Where workload and motivation have an effect of 49.2%